(untitled) (Molecular Medicine Communications, 2024)
Piperine is a phytocompound found in black and long pepper (Piper nigrum and Piper longum, respectively). It has several important pharmacological properties. The current study aimed to evaluate piperine for analgesic, anti-inflammatory, and anti-platelet activities. The analgesic and anti-inflammatory effects were assessed in mice and rats respectively using acetic acid and formalin-induced nociception, and carrageenan-induced rat paw edema tests. The intraperitoneal (i.p.) administration of the Piperine (10, 50, and 100 µg/kg) produced significant inhibition (P\0.01) of the acetic acid-induced writhing in mice and suppressed formalin-induced licking response of animals. Piperine (10, 50, and 100 µg/kg) produced a marked anti-inflammatory effect in carrageenan-induced rat paw edema assay comparable to diclofenac and produced a dose-dependent (1,5, and 10µM) inhibitory effect against arachidonic acid and adenosine diphosphate-induced platelet aggregation. However, piperine was less potent against the platelet aggregation induced by the platelet-activating factor and epinephrine. These data suggest that piperine possesses peripheral analgesic and anti-inflammatory properties, with potent antiplatelet effects against arachidonic acid and adenosine diphosphate.